Through-thickness thermal conductivity enhancement of carbon fiber composite laminate by filler network. (July 2019) - Fang, Zenong; Li, Min; Wang, Shaokai; Gu, Yizhuo; Li, Yanxia; Zhang, Zuoguang
Graphical abstract: Highlights: Highly conductive filler network is constructed to enhance through-thickness TC of composite laminate. Infrared thermography and FEA reveal heat transport mechanism of modified composites with different fillers and ply schemes. A through-thickness TC of up to 2.21 W·m −1 K −1 is achieved. Abstract: This paper successfully introduces highly conductive filler network in composite laminate to enhance its through-thickness thermal conductivity (TC). The effects of filler type, filler content, filler dimension, and ply scheme on through-thickness TC are investigated. The results show that one-dimensional carbon fiber fillers occupy both interlaminar and inter-tow regions forming the river-pattern conductive network inside the modified composite. Hence, the through-thickness TC is enhanced effectively up to 2.21 W·m −1 K −1 for the carbon fiber filler modified composite, which increases with increasing filler content. The composites modified by shorter fiber fillers show higher through-thickness TCs than those modified by long fillers, due to relatively higher content of shorter fillers in inter-tow gap, easy orientation along through-thickness direction and higher filler volume faction in conductive path. These results prove the superiority of continuous conductive network with concentrated fillers, and guide the structural design of composite laminate to manage its through-thickness TC.